Critical heat flux enhancement of pool boiling using a porous nanostructured coating. Issue 4 (4th July 2017) - Nazari, Ahmad; Saedodin, Seyfolah
ABSTRACT: Surface coating techniques are commonly used to increase heat transfer and control critical heat flux. In this research, we used anodizing—an electrochemical coating process—to coat an aluminum oxide layer on the aluminum plain surface. This porous nanostructured coating has uniform, cylindrical, parallel nanochannels, and closed end pores. Next, we conducted saturated pool boiling tests on the anodized samples, using deionized water and the CHFs were measured. We found that porous nanostructured coatings, due to their improved surface characteristics, particularly wettability, increased CHF values and also critical heat flux increased linearly with decreasing the contact angle.